I remain in darkness - Ernaux, Annie, 1940- (Seven Stories Press, 1999)
A woman suffering from Alzheimer's disease is taken in by her daughter who records her decline. The daughter narrates, "Today she was holding a corner of her blouse (smock), clutching onto it. In the elevator, she stood facing the mirror. I am sure she could see herself." By a French writer, author of Simple Passion.